Effect of a 5‐HT2c receptor agonist on urethral closure mechanisms in female rats. Issue 8 (6th April 2018) - Ouchi, Mifuka; Kitta, Takeya; Kanno, Yukiko; Higuchi, Madoka; Togo, Mio; Moriya, Kimihiko; Shinohara, Nobuo
Abstract : Aims: The serotonin (5‐HT2c) receptor is known to be involved in the mechanism of urethral closure in a model of stress incontinence. Lorcaserin (Belviq®) has received Food and Drug Administration approval for the treatment of obesity. However, it is unclear whether this selective 5‐HT2c receptor agonist enhances urethral closure in stress urinary incontinence (SUI) models. Therefore, we investigated whether lorcaserin could enhance urethral closure in female rats with vaginal distention (VD). Methods: Normal female rats and rats with stress incontinence induced by VD were tested. We evaluated the effect of a single dose of lorcaserin (0.03, 0.3, or 0.9 mg/kg with cumulative administration) on the urethral pressure amplitude during electrical stimulation (A‐URE) and on the urethral baseline pressure (UBP). The manual compression‐induced leak point pressure (LPP) was also measured. Results: In VD rats, a single intravenous injection of lorcaserin (0.3 and 0.9 mg/kg) significantly increased both A‐URE and LPP compared to saline ( P  < 0.05). In normal rats, intravenous lorcaserin (0.3 and 0.9 mg/kg) also significantly increased A‐URE and LPP compared to saline ( P  < 0.05). The changes of A‐URE and LPP, which are parameters of active urethral closure, were significantly larger in normal rats than in VD rats. Conclusions: We showed that lorcaserin can activate the external urethral sphincter and pelvic floor muscles, suggesting an influence on active closure mechanisms. 5‐HT2c receptors agonists may have dual effects in patients with SUI, not only by reducing obesity but also by enhancing active urethral closure.